Humanistic Education in The Society 5.0 Era: Building Adaptive Competence and Character - Parham Taufik; Ramdani Sidik; Ahmad Hidayat; Ummul Muminin (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
This article aims to analyze the relevance and strategic role of the Humanistic Education Approach in shaping strong and morally good competencies and character among students, particularly in facing the disruptions of the Society 5.0 Era. The background of this research is based on the paradox between rapid technological advancements and the emergence of moral and ethical crises in the education sector, evidenced by the increasing cases of students' disrespect towards teachers. Through a qualitative literature study, the humanistic approach is seen as an antithesis to the pragmatic education model that neglects students' potential and humanity. The research results show that humanistic principles, which view students as whole subjects oriented towards self-actualization, are vital for balancing the dominance of technology. Its implementation requires transforming the role of teachers into facilitators and dialogue partners who guide students not only in intellectual aspects but also in the internalization process of attitudes, values, and morality.